The Effect of Visual Media to Promote Awareness of the Israeli-Palestinian Conflict (Journal of Governance and Development (JGD), 2015)
The researchers shed light on the ability of visual media to raise awareness that contributes to change within governments or major decisions in the countries. It also discusses the media’s state of being able to reach directly to the citizens and if there is any need to have an intermediary that is required to work alongside the media such as political elites and political parties. In addition, this study attempts to find out the media’s effectiveness in raising awareness of the issue of Palestine to groups of university students in countries surrounding Palestine and how it contributes to Israel’s fate and being threatened for being involved with Palestinians.